Peran Pendidikan Agama Islam Dalam Membangun Moderasi Beragama Di SD Negeri 18 Kalosi - Sri Bulan; Harni Kadang; Anita. S; Jusrianti Jusrianti; Amaluddin Amaluddin (Prodi PGSD Unsultra, 2025)
This study aims to describe the implementation of religious moderation in Islamic Religious Education (PAI) at SD Negeri 18 Kalosi and examine how teachers integrate moderation values into learning to strengthen students' character. Data were collected through observation, interviews, and documentation to capture classroom dynamics and the school's support for developing moderate attitudes. Findings show that teachers apply varied strategies, including contextual explanations, group discussions, role modeling, and positive behavioral habits, to promote tolerance, respect for differences, and cooperation. School programs, such as inclusive religious activities, character-building routines, and community service, further reinforce these values through practical experiences. As a result, students demonstrate increasingly moderate behavior, including empathy, collaboration, and respect for diversity. The study highlights that the synergy between teacher practices and supportive school programs is essential for effectively internalizing moderation values in students.